2020
DOI: 10.33395/owner.v4i2.309
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan, GPM, Risiko Bisnis terhadap Struktur Modal pada Perusahaan Manufaktur di BEI

Abstract: Perkembangan ekonomi di Negara sedang mengalami pertumbuhan yang cukup pesat pada era globalisasi, ini sangat jelas terlihat dikebanyakan perusahaan yang saat ini bertumbuh cepat. Melihat perkembangan zaman,semakin banyak masalah yang timbul sehingga membuat para investor semakin tidak tertarik untuk menanamkan modalnya. Perusahaan akan sangat membutuhkan dana demi kelangsungan hidup industrinya,dengan adanya struktur modal yang efisien akan lebih memudahkan jalannya suatu operasi industri tersebut.Tujuan dari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of testing the hypothesis can be concluded that company size has no influence on the company's business risk. These results are supported by research conducted by (Damayanti & Dana, 2017) and also (Meilyani et al, 2019) which states that company size has no effect on business risk. This is because at this time investors do not only see the number of assets owned by the company, but investors are now more concerned with the future prospects of the company.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of testing the hypothesis can be concluded that company size has no influence on the company's business risk. These results are supported by research conducted by (Damayanti & Dana, 2017) and also (Meilyani et al, 2019) which states that company size has no effect on business risk. This is because at this time investors do not only see the number of assets owned by the company, but investors are now more concerned with the future prospects of the company.…”
Section: Discussionsupporting
confidence: 60%
“…company size has a positive effect on the business risk owned by the company. The comes about of this think about are bolstered by investigate conducted by (Damayanti & Dana, 2017). Similar research by (Primantara & Dewi, 2016) stated that company size has a positive influence on business risk…”
Section: Theoritical Frame Workmentioning
confidence: 86%
“…According to the study conducted by Purnasari et al, (2020), it was found that the size of a corporation not only affects its magnitude but also represents a number of aspects that possess an influence. When it comes to gaining access to external financial resources, large corporations have their own set of benefits.…”
Section: Introductionmentioning
confidence: 99%
“…If the funds come from large debts, then the risk that company has is also large ones. If the company does not want to have large operating risks, it can reduce the debt level to avoid the large risks that the company will face (Purnasari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%